Challenging The City Scale. Milan (2018)
Walking around “La Piana” can feel like walking around hundreds of city suburbs all over Europe. Residential buildings surround the large, empty space on top of a car park which is located on street level. When you’re here, it’s hard to tell if you’re in a private or public space, inside or outside the city. Right next to this empty 10,000 square metre space, Nadia Fulco co-founded the 200-seat Ringhiera Theatre in 2007. It was a huge challenge in an area that was far away from the city centre and that suffered from a general lack of cultural activities and events. During the next ten years, the ATIR1 association worked closely with the local community and organised countless activities, especially for children, teenagers, older people and people with disabilities. The activities were carried out in parallel to the theatre’s on-stage events and helped to create synergies. As a result, “we managed to build a vibrant community,” says Nadia Fulco, who is responsible for ATIR’s social projects. “A lot of the residents regularly come to our plays.”